Friction body, brake pad and preparation method of friction body

The friction body with copper-iron alloy and recarburizer particles addresses heat transfer issues in carbon ceramic brake discs, ensuring stable performance and reduced wear in hydrogen energy trains through enhanced thermal conductivity and self-cleaning.

CN119144884APending Publication Date: 2024-12-17BEIJING PURAN RAIL TRANSIT TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411086737.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Carbon ceramic brake discs in hydrogen energy trains suffer from poor heat transfer, leading to high temperatures that soften the copper matrix of brake pads, causing mechanical and friction property failures, increased wear, and particle cracking during high-speed and high-pressure braking.

Method used

A friction body composed of copper-iron alloy powder with semi-graphitized recarburizer particles, along with specific friction and stabilizing components, is formulated and processed through high-speed mixing, cold pressing, and pressure sintering to enhance thermal conductivity, mechanical strength, and self-cleaning properties.

Benefits of technology

The friction body maintains stable shape and performance under high temperature and pressure, reduces wear, and ensures a consistent friction coefficient, with self-cleaning capabilities and a long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144884A_ABST
    Figure CN119144884A_ABST
Patent Text Reader

Abstract

The invention discloses a friction body, a brake pad and a preparation method of the friction body, and aims to solve the problems that the friction coefficient of the brake pad declines, abrasion is sharply increased, and even friction particles crack and fall off when a hydrogen energy train is continuously and emergently braked at high speed and high pressure. The friction body is prepared from the following raw material components in percentage by weight: 60wt%-75wt% of a matrix component, 11wt%-16wt% of a friction component, 12wt%-20wt% of a reinforcing component and 2wt%-4wt% of a stable component, wherein the base body comprises copper alloy powder, iron alloy powder and alloyed copper-iron alloy powder, according to the weight percentage of the friction body, the adding amount of the copper alloy powder accounts for 40 wt%-50 wt% of the weight percentage of the friction body, and the adding amount of the iron alloy powder accounts for 20 wt%-25 wt% of the weight percentage of the friction body; and the reinforcing component comprises semi-graphitized carburant particles. The friction body disclosed by the invention has good temperature resistance and recession resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a friction body, a brake pad and a preparation method thereof, and belongs to the technical field of train braking. Background Art

[0002] With the lightweight of trains, the demand for clean energy and the development of high-speed rail braking, carbon ceramic brake discs used in hydrogen energy urban trains have gradually matured. Compared with cast steel discs, carbon ceramic discs are light in weight, have a long service life, are resistant to high temperatures, have low noise, are clean and environmentally friendly, and have strong corrosion resistance. However, the heat transfer effect of carbon ceramic discs used in hydrogen energy trains is poor. Most of the large amount of heat energy generated by friction during braking is transferred from the disc to the brake pads, and the instantaneous temperature is as high as 800℃~1000℃. With the increase of braking speed, braking pressure, axle weight and disc load, greater stress is generated on the brake pads. Under this service condition, the copper matrix of the brake pads will soften, resulting in the failure of its high temperature mechanical properties and friction properties, especially during continuous emergency braking at high speed and high pressure. The friction coefficient declines, the wear increases sharply, and even the friction particles crack and collapse and fall off. Summary of the invention

[0003] The purpose of the present invention is to provide a friction body, a brake pad and a preparation method thereof in view of the drawbacks of the prior art, so as to solve the problem of poor heat resistance of the existing brake pads during the braking process of the carbon-ceramic brake disc used in hydrogen-powered urban trains.

[0004] The problem of the present invention is achieved by the following technical solutions:

[0005] In the first aspect, the present invention discloses a friction body, which is prepared from the following raw material components, calculated by weight percentage of the friction body: a matrix component of 60wt% to 75wt%, a friction component of 11wt% to 16wt%, a reinforcing component of 12wt% to 20wt% and a stabilizing component of 2wt% to 4wt%; wherein the matrix component is copper alloy powder and iron alloy powder, and the alloyed copper-iron alloy powder, calculated by weight percentage of the friction body, has an addition amount of copper alloy powder accounting for 40wt% to 50wt% of the weight percentage of the friction body, and an addition amount of iron alloy powder accounting for 20wt% to 25wt% of the weight percentage of the friction body; and the reinforcing component includes semi-graphitized carburizer particles.

[0006] Compared with the prior art, the weight percentage of the copper alloy powder in the present invention is 40wt%-50wt%, and the weight percentage of the iron alloy powder is 20wt%-25wt%. The weight percentage of the iron alloy in the present invention accounts for about 1 / 3 of the total weight percentage of the copper-iron alloy. By matching and reasonably proportioning the copper alloy powder and the iron alloy powder, the ductility and thermal conductivity of the copper alloy matrix and the high melting point, good mechanical strength and hardness of the iron alloy matrix are fully utilized, so that the friction body has both advantages, ensuring that the brake pad can maintain a stable shape and performance under high temperature and high pressure conditions during braking, and is more suitable for high temperature and high pressure service conditions during braking of hydrogen energy trains; the present invention uses Semi-graphitized recarburizer particles are used as reinforcing components. The introduction of carbon elements can change the properties of the alloy, which is beneficial to enhancing the strength and hardness of the brake pad. In addition, the sulfur element in the semi-graphitized recarburizer particles can generate copper sulfide and ferrous sulfide respectively with the copper element and the iron element. During the braking process of the train, due to the increase in friction temperature, the copper sulfide and ferrous sulfide will melt to form a film. The film can eliminate the adhesion and sticking of the friction pair, make the brake pad self-cleaning, and can protect the surface of the brake pad. It also helps to maintain a stable friction coefficient, ensure the stability of the friction coefficient of the brake pad under high temperature and high pressure conditions during braking, and can also improve the wear resistance of the brake pad, which is beneficial to reduce the wear of the brake pad.

[0007] The friction body of the present invention adopts metal powder as raw material, does not contain organic matter, has strong stability, can be stored naturally for a long time without affecting its friction performance, and has a long service life.

[0008] Furthermore, the copper alloy powder includes copper powder and tin powder, in which the tin powder accounts for 4wt% to 6wt% of the copper alloy powder by weight; the iron alloy powder includes iron powder and nickel powder, in which the nickel powder accounts for 4wt% to 6wt% of the iron alloy powder by weight.

[0009] Furthermore, the friction components include a main friction component and a secondary friction component, the main friction component includes high carbon ferrochrome, and the secondary friction component includes any one of aluminum oxide, zirconium oxide, and titanium oxide; the stabilizing component includes molybdenum powder and tungsten powder.

[0010] Furthermore, in terms of weight percentage of the friction body, the weight percentage of the main friction component is 9wt% to 12wt%, and the weight percentage of the secondary friction component is 2wt% to 4wt%.

[0011] Furthermore, the particle size of the semi-graphitized recarburizer particles is 30 to 100 meshes, and the sulfur content of the semi-graphitized recarburizer particles is 0.1 to 0.3%;

[0012] and / or, the particle size of high carbon ferrochrome is ≤ 60 mesh, the chromium content of the high carbon ferrochrome is 68% to 73%, the carbon content is 7% to 9%, the iron content is 20% to 23%, and the particle sizes of alumina, zirconium oxide and titanium oxide are all 100 to 200 mesh;

[0013] And / or, the particle size of the molybdenum powder is ≤325 mesh, and the particle size of the tungsten powder is ≤325 mesh.

[0014] In a second aspect, the present invention discloses a method for preparing a friction body, which is applied to the above-mentioned friction body, comprising:

[0015] According to the proportion, copper powder and tin powder are mixed at a high speed of 1000 rpm to 3000 rpm for 3 to 5 minutes to obtain copper alloy powder, and iron powder and nickel powder are mixed at a high speed of 1000 rpm to 3000 rpm for 3 to 5 minutes to obtain iron alloy powder;

[0016] The semi-graphitized carburizer, copper alloy powder and iron alloy powder are mixed by internal kneading, the mixing speed is set to 15 rpm to 30 rpm, the mixing time is set to 10 to 20 min, and the internal kneading temperature is set to 0 to 80° C. to obtain a mixed powder;

[0017] The stabilizing component, the friction component, the alloyed mixed powder and the binder are mixed in a V-shape, the mixing speed is set to 15 rpm to 30 rpm, and the mixing time is set to 40 to 50 min to obtain a mixed total powder;

[0018] The mixed total powder is placed in a mold at room temperature for high pressure molding, the pressure is set to 7Mpa-15Mpa, the pressure holding time is 3-10 seconds, and a friction body green body is obtained, which is then formed into a friction body through pressure sintering.

[0019] Compared with the prior art, the preparation method of the friction body in the present invention fully mixes the components through high-speed mixing, banburying mixing and V-type mixing, thereby improving the uniformity of material mixing, shortening the mixing cycle, and improving production efficiency. Then, through cold pressing and pressure sintering, the physical and mechanical properties and wear resistance of the product are effectively enhanced. The preparation method of the friction body of the present invention has a simple process and is suitable for industrial production.

[0020] Furthermore, the binder is kerosene, and the amount of the binder added is 0.7wt% of the total amount of the mixed powder.

[0021] In a third aspect, the present invention discloses a brake pad, comprising a steel back and friction particles, wherein the friction particles comprise a skeleton and the above-mentioned friction body, wherein the friction body is fixed on the skeleton; and the friction particles are fixed on the steel back through the skeleton.

[0022] Compared with the prior art, the brake pad of the present invention has good mechanical strength, does not damage the brake disc, has self-cleaning properties, still has good mechanical properties and wear resistance under high temperature conditions, can ensure a stable friction coefficient, and can meet the needs of brake pads under high-speed braking of trains.

[0023] In a fourth aspect, the present invention discloses a method for preparing a brake pad, which is applied to the above-mentioned brake pad, comprising the following steps:

[0024] Prepare the steel back and frame;

[0025] The friction body green body and the skeleton are pressurized and sintered under the protection of protective gas to obtain friction particles;

[0026] The friction particles are fixed on the steel back to obtain the brake pad.

[0027] Compared with the prior art, the preparation method of the brake pad of the present invention performs pressure sintering treatment on the friction body, which can improve the density and strength of the material, optimize the friction and heat conduction properties, and improve the heat resistance of the friction body under high temperature conditions, which helps the brake pad to maintain stable friction performance and mechanical strength under train braking conditions.

[0028] Further, the friction body green body and the skeleton are pressurized and sintered, including:

[0029] The friction body green body and the skeleton are placed in a chain belt type pressure sintering furnace for sintering. When the chain belt type pressure sintering furnace is opened, a protective atmosphere is first introduced, the chain belt speed is set to 60 mm / min, the sintering pressure is set to 0.1-0.2 MPa, and the sintering adopts a segmented step-by-step temperature increase. When each segment reaches the set temperature of the segment, the product is placed on the chain belt and pressurized for sintering. The segmented step-by-step temperature increase specifically includes:

[0030] The chain-belt pressure sintering furnace is divided into four sections. The first section is 1200mm, with a temperature of 300℃~500℃, the second section is 1200mm, with a temperature of 500℃~700℃, the third section is 1200mm, with a temperature of 500℃~700℃, and the fourth section is 3600mm, with a temperature of 900℃~1100℃. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0032] Figure 1 A cross-sectional schematic diagram of a brake pad provided by an embodiment of the present invention;

[0033] Figure 2 A schematic cross-sectional view of a friction particle provided by an embodiment of the present invention;

[0034] Figure 3 A schematic top view of a friction particle provided by an embodiment of the present invention;

[0035] Figure 4 A schematic diagram of the structure of a steel back provided by an embodiment of the present invention;

[0036] Figure 5 A schematic structural diagram of a brake pad provided in an embodiment of the present invention.

[0037] Figure numerals: 1 is a steel back; 2 is a retaining spring; 3 is a friction particle; 31 is a frame; 311 is a locking pin; 312 is a connecting piece; 32 is a friction body; 4 is a disc-shaped spring. DETAILED DESCRIPTION

[0038] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.

[0040] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.

[0041] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by the terms "up", "down", "front", "back", "left", "right", etc. are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.

[0042] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0043] In the prior art, with the lightweight of trains, the demand for clean energy and the development of high-speed rail braking, carbon ceramic brake discs used in hydrogen energy urban trains have gradually matured. Compared with cast steel discs, carbon ceramic discs are light in weight, have a long service life, are resistant to high temperatures, have low noise, are clean and environmentally friendly, and have strong corrosion resistance. However, the heat transfer effect of carbon ceramic discs used in hydrogen energy trains is poor. Most of the large amount of heat energy generated by friction during braking is transferred from the disc to the brake pads, and the instantaneous temperature is as high as 800℃~1000℃. With the increase of braking speed, braking pressure, axle weight and disc load, greater stress is generated on the brake pads. Under this service condition, the copper matrix of the brake pads will soften, resulting in the failure of its high temperature mechanical properties and friction properties, especially during continuous emergency braking at high speed and high pressure. The friction coefficient declines, the wear increases sharply, and even the friction particles crack and collapse and fall off.

[0044] In view of this problem, the present invention provides a friction body, a brake pad and a preparation method thereof.

[0045] In the first aspect, an embodiment of the present invention provides a friction body, which is prepared from the following raw material components, measured in weight percentage of the friction body: a matrix component of 60wt% to 75wt%, a friction component of 11wt% to 16wt%, a reinforcing component of 12wt% to 20wt% and a stabilizing component of 2wt% to 4wt%; wherein the matrix component is copper-iron alloy powder alloyed with copper alloy powder and iron alloy powder, and measured in weight percentage of the friction body, the added amount of copper alloy powder accounts for 40wt% to 50wt% of the weight percentage of the friction body, and the added amount of iron alloy powder accounts for 20wt% to 25wt% of the weight percentage of the friction body; the reinforcing component includes semi-graphitized carburizer particles.

[0046] By adopting the above technical scheme, in the friction body of the above embodiment, the added amount of copper alloy powder accounts for 40wt% to 50wt% of the weight percentage of the friction body, and the added amount of iron alloy powder accounts for 20wt% to 25wt% of the weight percentage of the friction body, and the copper alloy has high thermal conductivity, good wear resistance and strength, which helps to quickly conduct the heat generated by friction, prevent the brake pad from overheating, and improve the wear resistance of the brake pad; the iron alloy has a higher melting point, good mechanical strength and hardness, which is beneficial for the brake pad to maintain a stable shape and performance under high pressure and high friction conditions. In the embodiment of the present invention, the iron alloy matrix accounts for about 1 / 3 of the total copper-iron alloy matrix. By matching and reasonably proportioning the copper alloy powder and the iron alloy powder, the thermal conductivity of the copper alloy matrix and the high melting point, good mechanical strength and hardness of the iron alloy matrix are fully utilized, so that the friction body has both advantages, ensuring that the brake pad can maintain a stable shape and performance under high temperature and high pressure conditions during braking, and is more suitable for high temperature and high pressure service conditions during braking of hydrogen energy trains; in the embodiment of the present invention, semi-graphitized recarburizer particles are used as reinforcing components, which can realize the introduction of carbon elements in the metal alloying process, can change the performance of the alloy, and is conducive to enhancing the strength and hardness of the brake pad, making it more durable , and the sulfur element in the semi-graphitized recarburizer particles can generate copper sulfide and ferrous sulfide with the copper element and iron element respectively. During the braking process of the train, due to the increase in friction temperature, copper sulfide and ferrous sulfide will melt to form a film. The film can eliminate the adhesion and jamming of the friction pair, making the brake pad self-cleaning. During use, the brake pad can automatically clean itself, reducing failures caused by dirt or debris, and can protect the surface of the brake pad to prevent cracking and collapse of friction particles caused by high temperature and high pressure. It also helps to maintain a stable friction coefficient, ensuring the stability of the friction coefficient of the brake pad under high temperature and high pressure conditions during braking, and can also improve the wear resistance of the brake pad, which is beneficial to reducing the wear of the brake pad.

[0047] The friction body in the above embodiment uses metal powder as raw material, does not contain organic matter, has strong stability, can be stored naturally for a long time without affecting its friction performance, and has a long service life.

[0048] Further, in combination with the above embodiments, the copper alloy powder in the embodiments of the present invention includes copper powder and tin powder, and the tin powder accounts for 4wt% to 6wt% of the copper alloy powder by weight percentage; the iron alloy powder includes iron powder and nickel powder, and the nickel powder accounts for 4wt% to 6wt% of the iron alloy powder by weight percentage. Copper has high thermal conductivity, which helps to quickly conduct and dissipate the heat generated by friction, prevent the brake pad from overheating, and improve the working efficiency and life of the brake pad; the mechanical strength of the copper matrix is ​​not high, but the alloying of copper and tin can achieve the strengthening of the copper matrix, and has good wear resistance and strength, which can improve the wear resistance of the brake pad and make the brake pad less likely to deform; iron has a high melting point, good mechanical strength and hardness, which is conducive to the brake pad to maintain a stable shape and performance under high pressure and high friction conditions, and the friction surface of the iron matrix can self-generate an oxide film when it contacts the air at high temperature, which plays a role in stabilizing the friction coefficient and protecting the matrix. However, under heavy load, high speed and high temperature, the high temperature strength of the iron matrix will also decline. The alloying of iron and nickel can achieve the strengthening of the iron matrix. The high temperature strength of the iron-nickel alloy under heavy load, high speed and high temperature can still remain stable.

[0049] Further, in combination with the above embodiments, the friction components in the embodiments of the present invention include a main friction component and a secondary friction component, the main friction component includes high carbon ferrochrome, and the secondary friction component includes any one of aluminum oxide, zirconium oxide, and titanium oxide; the stabilizing component includes molybdenum powder and tungsten powder. As the main friction component, high carbon ferrochrome has good high temperature stability, hardness and wear resistance, can maintain the strength and hardness of the brake pad at high temperature, and make the brake pad withstand high pressure and frequent friction without easy wear, which is suitable for the high temperature environment generated by the brake system during high-speed braking; among the secondary friction components, aluminum oxide has wear resistance and high thermal conductivity, can reduce friction loss under high friction conditions, effectively dissipate the heat generated during braking, and extend the service life of the brake pad; zirconium oxide has excellent thermal shock resistance, high temperature stability and high hardness, and can maintain the stability of the brake pad under high load and high temperature conditions; titanium oxide has good high temperature resistance, wear resistance and fatigue resistance, can improve the wear resistance and fatigue resistance of the brake pad, enhance the stability and performance under high temperature conditions, and extend the service life of the brake pad, and the Mohs hardness of high carbon ferrochrome is 5, the Mohs hardness of aluminum oxide is 7, the Mohs hardness of zirconium oxide is 8, and the Mohs hardness of titanium oxide is 6. Using medium hardness materials with Mohs hardness between 5 and 8 as the friction component of the brake pad is conducive to ensuring the stability of the friction coefficient and reducing wear. Molybdenum powder and tungsten powder are used as stable components. Molybdenum has good high-temperature stability, and molybdenum and iron can form Mo-Fe solid solution. Mo-Fe solid solution can improve the hardness, strength and wear resistance of the material, and can maintain the structure and performance of the brake pad stable at extremely high temperatures. The melting point of tungsten is as high as 3422℃. Adding tungsten helps to improve the high-temperature resistance of the material and reduce wear at high temperatures. Tungsten has high thermal conductivity, which helps the brake pad to quickly conduct heat during braking and reduce local overheating of the brake pad, thereby protecting the braking system.

[0050] Further, in combination with the above embodiment, in the embodiment of the present invention, the weight percentage of the main friction component is 9wt% to 12wt%, and the weight percentage of the secondary friction component is 2wt% to 4wt%.

[0051] Further, in combination with the above-mentioned embodiment, the particle size of the semi-graphitized recarburizer particles in the embodiment of the present invention is 30-100 meshes, and the sulfur content of the semi-graphitized recarburizer particles is 0.1wt%-0.3wt%;

[0052] and / or, the particle size of the high carbon ferrochrome is ≤60 meshes, the chromium content of the high carbon ferrochrome is 68wt% to 73wt%, the carbon content is 7wt% to 9wt%, the iron content is 20wt% to 23wt%, and the particle sizes of aluminum oxide, zirconium oxide and titanium oxide are all 100 to 200 meshes;

[0053] And / or, the particle size of the molybdenum powder is ≤325 mesh, and the particle size of the tungsten powder is ≤325 mesh.

[0054] By adopting the above technical solution, by limiting the particle size and specific proportion of the above components, the various components of the friction body can better cooperate with each other, thereby improving the heat resistance and mechanical strength of the friction body, and making the friction body with a specific composition have excellent heat resistance.

[0055] In a second aspect, an embodiment of the present invention provides a method for preparing a friction body, which is applied to the above-mentioned friction body, comprising:

[0056] According to the proportion, copper powder and tin powder are mixed at a high speed of 1000 rpm to 3000 rpm for 3 to 5 minutes to obtain copper alloy powder, and iron powder and nickel powder are mixed at a high speed of 1000 rpm to 3000 rpm for 3 to 5 minutes to obtain iron alloy powder;

[0057] The semi-graphitized recarburizer particles, copper alloy powder and iron alloy powder are mixed by internal kneading, the mixing speed is set to 15 rpm to 30 rpm, the mixing time is set to 10 to 20 min, and the internal kneading temperature is set to 0 to 80° C. to obtain a mixed powder;

[0058] The stabilizing component, the friction component, the alloyed mixed powder and the binder are mixed in a V-shape, the mixing speed is set to 15 rpm to 30 rpm, and the mixing time is set to 40 to 50 min to obtain a mixed total powder;

[0059] The mixed total powder is placed in a mold at room temperature for high pressure molding, the pressure is set to 7MPa-15MPa, the pressure holding time is 3-10 seconds, and a friction body green body is obtained, which is then formed into a friction body through pressure sintering.

[0060] It should be understood that in the above technical solution, copper powder is the source of copper element in the alloying metal, iron powder is the source of iron element, tin powder is the source of tin element, and nickel powder is the source of nickel element. During the preparation process, the particle size of copper powder is controlled to be ≤200 mesh, the particle size of iron powder is ≤200 mesh, the particle size of tin powder is ≤325 mesh, and the particle size of nickel powder is ≤325 mesh. Smaller particle size helps to achieve uniform distribution of raw material components in the powder, thereby ensuring the consistency and stable performance of the friction body.

[0061] Adopting the above technical scheme, the above embodiment first uses a high-speed mixer to mix copper powder and tin powder, iron powder and nickel powder at high speed. The high-speed mixing can achieve rapid and uniform mixing of materials through high-speed mechanical movement, ensuring that each component is evenly distributed, thereby improving the performance consistency and reliability of the brake pad. In the embodiment of the present invention, a horizontal grid drum is used for internal mixing. The internal mixing mixture ensures the full mixing of metal powder and other components through the mechanical stirring action of the grid, and the efficient mixing during the mixing process makes the material more compressible and sinterable, thereby improving the compressive strength and wear resistance of the brake pad. V-type mixing can ensure the uniform mixing of metal powder and other ingredients, ensure the uniform distribution of metal powder and other ingredients, avoid material segregation, and thus ensure the consistency and stable performance of each brake pad. In the embodiment of the present invention, the mixed total powder is directly pressed into the desired shape to obtain a friction body green body, which can effectively improve the uniformity and performance of the product, and the process is relatively simple, the operation is easy to master, and it is suitable for large-scale production.

[0062] Further, in combination with the above embodiment, the binder in the embodiment of the present invention is kerosene, and the amount of the binder added is 0.7wt% of the total amount of the alloyed mixed powder. In the mixing process, kerosene can dilute the powder, reduce the agglomeration phenomenon between the powder particles, and make the mixing more uniform. In addition, kerosene has the properties of penetration and lubrication, which can reduce the friction between the powder particles and help the powder to be more evenly dispersed in the mixer, thereby helping to enhance the performance consistency of the friction body and improve the overall strength and toughness of the friction body.

[0063] Third, please refer to Figures 1 to 5 An embodiment of the present invention provides a brake pad, including a steel back 1 and friction particles 3. The friction particles 3 include a skeleton 31 and a friction body 32. The friction body 32 is fixed on the skeleton 31. The friction particles 3 are fixed on the steel back 1 through the skeleton 31.

[0064] By adopting the above technical scheme, the brake pad provided by the embodiment of the present invention has good mechanical strength, does not damage the brake disc, and has self-cleaning properties, so that the brake pad can be automatically cleaned during use. The brake pad still has good mechanical properties and wear resistance under high temperature conditions, can prevent the cracking and collapse of friction particles caused by high temperature and high pressure, and can also ensure a stable friction coefficient, which can meet the needs of brake pads under high-speed braking of trains.

[0065] Further, it should be understood that when the friction body is fixed to the frame, the connection method between the friction body 32 and the frame 31 can adopt the commonly used fixing method in the prior art. Figure 1 and Figure 2One of the fixing methods of the friction body 32 to the frame 31 can be referred to as follows: In the embodiment of the present invention, the frame 31 includes a locking pin 311 and a connecting piece 312. The locking pin 311 and the connecting piece 312 are an integral structure. A group of positioning holes are symmetrically opened along the center line on the connecting piece 312. A positioning column matched with the positioning hole is provided on the friction body 32. The friction body 32 and the connecting piece 312 are welded by pressure sintering after being assembled through the positioning column and the positioning hole. The connecting piece 312 and the locking pin 311 are an integral structure, which makes the entire frame more stable and not easy to deform. In addition, the cooperation of the positioning hole and the positioning column makes the connection between the friction body and the connecting piece tighter, further improving the stability of the overall structure.

[0066] Furthermore, it should be understood that when the friction particles are fixed to the steel back through the frame, the fixing connection method of the friction particles and the steel back can adopt the fixing method commonly used in the prior art. For example, in the embodiment of the present invention, when the friction particles are fixed to the steel back, the fixing is performed by setting a matching structure between the friction particle frame and the steel back. Specifically, Figure 1 As shown, in the embodiment of the present invention, the steel back is a dovetail pin type steel back, a plurality of disc-shaped spring pieces 4 are arranged on one side of the steel back 1, a plurality of locking holes matched with the locking pins 311 of the friction particles 3 are opened on the steel back 1, and the locking pins 311 of the friction particles 3 are correspondingly inserted into the disc-shaped spring pieces 4 and the locking holes and then locked with the retaining spring 2 to form a brake pad. In the embodiment of the present invention, the disc-shaped spring pieces 4 and the retaining spring 2 are matched to improve the uniform contact between each friction particle of the brake pad and the brake disc surface during the braking process, improve the braking heat distribution and thus improve the uneven wear, improve the braking efficiency, and reduce the braking noise caused by the uneven braking hot spots on the disc surface.

[0067] Furthermore, in combination with the above embodiments, the shape of the friction particles in the embodiments of the present invention can be a regular hexagon, or can be adjusted to other shapes according to the use requirements. By rationally designing the friction particles of the brake pad, it is possible to reduce excessive friction between the brake pad and the brake disc in a friction ring, alleviate the uneven distribution of high temperature and uneven wear of the disc surface, and at the same time, more uniform contact is conducive to smooth friction of the friction pair, avoiding abnormal vibration and noise.

[0068] In a fourth aspect, an embodiment of the present invention provides a method for preparing a brake pad, which is used to prepare the above-mentioned brake pad, comprising the following steps:

[0069] Prepare the steel back and frame;

[0070] The friction body green body and the skeleton are pressurized and sintered under the protection of protective gas to obtain friction particles;

[0071] The friction particles are fixed on the steel back to obtain the brake pad.

[0072] By adopting the above technical solution, the friction body is subjected to pressure sintering treatment in the embodiment of the present invention, so that the connection between the metal powder particles is strengthened, thereby significantly improving the compressive and tensile strength of the material. The sintering treatment is conducive to combining the copper-iron metal matrix into a network, thereby improving the strength of the material. This not only enhances the mechanical properties of the brake pad, but also ensures the uniformity of its microstructure and performance, avoiding uneven wear during braking.

[0073] Further, in combination with the above embodiment, in the embodiment of the present invention, the friction body green body and the skeleton are pressurized and sintered, including:

[0074] The friction body green body and the skeleton are placed in a chain belt pressure sintering furnace for sintering. When the chain belt pressure sintering furnace is opened, a protective atmosphere is first introduced. The chain belt speed is set to 60mm / min, and the sintering pressure is set to 0.1-0.2MPa. The sintering adopts a segmented step-by-step temperature increase. When each segment reaches the set temperature of the segment, the product is placed on the chain belt and pressurized for sintering. The segmented step-by-step temperature increase specifically includes:

[0075] The chain-belt pressure sintering furnace is divided into four sections. The first section is 1200mm, with a temperature of 300℃~500℃, the second section is 1200mm, with a temperature of 500℃~700℃, the third section is 1200mm, with a temperature of 500℃~700℃, and the fourth section is 3600mm, with a temperature of 900℃~1100℃.

[0076] By adopting the above technical solution, the embodiment of the present invention uses segmented sintering, and by controlling the heating and holding time of different temperature sections, the particles inside the material can be more evenly combined, reducing the porosity and internal stress. This uniformity not only improves the overall performance of the brake pad, but also ensures the reliability and stability during braking. Segmented sintering can effectively control the microstructure of the material, which is conducive to stabilizing the friction coefficient of the brake pad and improving the wear resistance of the brake pad, thereby maintaining the good performance of the brake pad under high speed and high pressure conditions.

[0077] Further, in combination with the above embodiments, the protective gas in the embodiments of the present invention is ammonia decomposition gas, which is a mixed gas of 1 part nitrogen and 3 parts hydrogen generated after ammonia decomposition. The use of ammonia decomposition gas can reduce costs, and the hydrogen in the ammonia decomposition gas has a strong reducing property, which can ensure that the metal components in the friction particles are not oxidized under high temperature conditions.

[0078] Further, in combination with the above embodiments, the embodiments of the present invention further include a cooling process after sintering, and the cooling process can be water cooling or water cooling plus air cooling. A circulating water cooling jacket is provided at the terminal of the chain belt furnace. The cooling efficiency of water cooling is high, and the cooling efficiency of air cooling alone is low. The circulating water cooling jacket is more efficient when combined with air cooling outside the jacket. The air is nitrogen or other inert gas.

[0079] Furthermore, in combination with the above-mentioned embodiment, the sintering process and the cooling process in the embodiment of the present invention are both protected by protective gas. In this environment, the metal powder particles are more firmly bonded, which is conducive to reducing non-net matrix defects in the material, improving the strength of the brake pad, and can effectively prevent the oxidation of the brake pad material during the sintering process, avoid the reduction of sintering strength, and help maintain the friction coefficient and wear performance of the friction material.

[0080] The friction body and brake pad provided by the present invention are further described in detail below in conjunction with the embodiments. The following embodiments are merely explanations of the present invention, not limitations. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The test methods used in the following embodiments are conventional methods unless otherwise specified; the raw materials used in the following implementation methods are commercially available raw materials unless otherwise specified.

[0081] Example 1

[0082] The embodiment of the present invention provides a brake pad for a hydrogen energy train, comprising a dovetail pin-shaped steel back and a plurality of friction particles, wherein the friction particles comprise a frame and a friction body, wherein the friction body is fixed to the frame, and the friction particles are fixed to the steel back through the frame. The fixed connection method of the steel back, the frame and the friction body can refer to the above content, and will not be repeated here.

[0083] The friction body is prepared from the following raw material components, based on the weight percentage of the friction body: 48wt% copper alloy powder, 24wt% iron alloy powder, 14wt% semi-graphitized carburizer particles, 1wt% molybdenum powder, 1wt% tungsten powder, 10wt% high carbon ferrochrome, and 2wt% alumina.

[0084] The copper alloy powder includes copper and tin elements, of which tin accounts for 4.1wt% of the copper alloy powder by weight; the iron alloy powder includes iron and nickel elements, of which nickel accounts for 4.2wt% of the iron alloy powder by weight.

[0085] The method for preparing a brake pad in an embodiment of the present invention comprises the following steps:

[0086] S1. Prepare steel back and frame;

[0087] S2. According to the proportion, copper powder and tin powder are put into a high-speed mixer for high-speed mixing to obtain copper alloy powder, the mixing time is set to 3min, the mixing speed is set to 3000rpm, and iron powder and nickel powder are mixed at high speed to obtain ferroalloy powder, the mixing time is set to 3min, and the mixing speed is set to 3000rpm;

[0088] S3, putting the semi-graphitized carburizer particles, copper alloy powder and ferroalloy powder into a horizontal grid drum mixer for internal kneading and mixing to obtain a mixed powder, the mixing time is set to 15 min, the internal kneading temperature is set to 60° C., and the mixing speed is set to 25 rpm;

[0089] S4, V-shaped mixing of the mixed powder, high carbon ferrochrome, alumina, molybdenum powder, tungsten powder and binder to obtain a final mixed total powder, the mixing time is set to 45 min, and the mixing speed is set to 25 rpm;

[0090] The binder is kerosene, and the amount of kerosene added is 0.7wt% of the total amount of the mixed powder.

[0091] S5, placing the mixed total powder in a mold at room temperature for high pressure molding, the high pressure molding pressure is 15 MPa, the holding time is 3 seconds, and the friction body green body is obtained;

[0092] S6. Place the friction body green body and the skeleton in a chain belt pressure sintering furnace for sintering. The chain belt speed is set to 60 mm / min, the sintering pressure is set to 0.2 MPa, and the sintering is performed by step-by-step heating. When each section reaches the set temperature of the section, the product is placed on the chain belt and pressurized for sintering. The step-by-step heating specifically includes:

[0093] The chain belt pressure sintering furnace is divided into four sections, the first section is 1200mm, the temperature is 500℃, the second section is 1200mm, the temperature is 700℃, the third section is 1200mm, the temperature is 700℃, and the fourth section is 3600mm, the temperature is 1100℃;

[0094] Then it is quickly cooled to below 20℃ by a cooling jacket and then taken out of the furnace. Ammonia decomposition gas is used for protection during the sintering and cooling processes. After sintering and cooling, friction particles are obtained.

[0095] S7. First, install the disc-shaped spring piece and the sound insulation pad into the disc-shaped spring piece installation groove with the locking hole on the front side of the steel back in sequence, then insert the friction particle locking pin through the sound insulation pad and the disc-shaped spring piece into the locking hole on the steel back in sequence, finally turn over the semi-finished brake pad, and insert the retaining spring into the thin neck of the locking pin to obtain the brake pad.

[0096] In the embodiment of the present invention, placing the friction body green body and the skeleton in a chain belt type pressure sintering furnace for heating and sintering includes:

[0097] The compositions and preparation methods of Examples 2 to 6 are substantially the same as those of Example 1, except that the amounts of components of the friction body and some control parameters of the preparation process are different.

[0098] Example 2

[0099] An embodiment of the present invention provides a brake pad for a hydrogen energy train, comprising a dovetail pin-shaped steel back and a plurality of friction particles, wherein the friction particles comprise a skeleton and a friction body, the friction body is fixed on the skeleton, and the friction particles are fixed on the steel back through the skeleton.

[0100] The friction body is prepared from the following raw material components, based on the weight percentage of the friction body: 45wt% copper alloy powder, 25wt% iron alloy powder, 13wt% semi-graphitized carburizer particles, 2wt% molybdenum powder, 1wt% tungsten powder, 11wt% high carbon ferrochrome, and 3wt% zirconium oxide.

[0101] The copper alloy powder includes copper and tin elements, of which tin accounts for 4.4wt% of the copper alloy powder by weight; the iron alloy powder includes iron and nickel elements, of which nickel accounts for 4wt% of the iron alloy powder by weight.

[0102] The method for preparing a brake pad in an embodiment of the present invention comprises the following steps:

[0103] S1. Prepare steel back and frame;

[0104] S2. According to the proportion, copper powder and tin powder are put into a high-speed mixer for high-speed mixing to obtain copper alloy powder, the mixing time is set to 4 min, the mixing speed is set to 2000 rpm, and iron powder and nickel powder are mixed at high speed to obtain ferroalloy powder, the mixing time is set to 5 min, and the mixing speed is set to 1500 rpm;

[0105] S3, putting the semi-graphitized recarburizer particles, copper alloy powder and ferroalloy powder into a horizontal grid drum mixer for internal kneading and mixing to obtain a mixed powder, the mixing time is set to 10 min, the internal kneading temperature is set to 80° C., and the mixing speed is set to 15 rpm;

[0106] S4, V-shaped mixing of the mixed powder, high carbon ferrochrome, alumina, molybdenum powder, tungsten powder and binder to obtain a final mixed total powder, the mixing time is set to 50 min, and the mixing speed is set to 15 rpm;

[0107] The binder is kerosene, and the amount of kerosene added is 0.7wt% of the total amount of the mixed powder.

[0108] S5, placing the mixed total powder in a mold at room temperature for high pressure molding, the high pressure molding pressure is 7 MPa, the holding time is 10 seconds, and the friction body green body is obtained;

[0109] S6. Place the friction body green body and the skeleton in a chain belt pressure sintering furnace for sintering. The chain belt speed is set to 60 mm / min, the sintering pressure is set to 0.1 MPa, and the sintering is performed by step-by-step heating. When each section reaches the set temperature of the section, the product is placed on the chain belt and pressurized for sintering. The step-by-step heating specifically includes:

[0110] The chain belt pressure sintering furnace is divided into four sections, the first section is 1200mm, the temperature is 300℃, the second section is 1200mm, the temperature is 500℃, the third section is 1200mm, the temperature is 500℃, and the fourth section is 3600mm, the temperature is 900℃;

[0111] Then it is quickly cooled to below 20℃ by a cooling jacket and then taken out of the furnace. Ammonia decomposition gas is used for protection during the sintering and cooling processes. After sintering and cooling, friction particles are obtained.

[0112] S7. First, install the disc-shaped spring piece and the sound insulation pad into the disc-shaped spring piece installation groove with the locking hole on the front side of the steel back in sequence, then insert the friction particle locking pin through the sound insulation pad and the disc-shaped spring piece into the locking hole on the steel back in sequence, finally turn over the semi-finished brake pad, and insert the retaining spring into the thin neck of the locking pin to obtain the brake pad for hydrogen energy train braking.

[0113] Example 3

[0114] An embodiment of the present invention provides a brake pad for a hydrogen energy train, comprising a dovetail pin-shaped steel back and a plurality of friction particles, wherein the friction particles comprise a skeleton and a friction body, the friction body is fixed on the skeleton, and the friction particles are fixed on the steel back through the skeleton.

[0115] The friction body is prepared from the following raw material components based on the weight percentage of the friction body: 50wt% copper alloy powder, 20wt% iron alloy powder, 16wt% semi-graphitized carburizer particles, 1wt% molybdenum powder, 1wt% tungsten powder, 9wt% high carbon ferrochrome, and 3wt% titanium oxide.

[0116] The copper alloy powder includes copper and tin elements, of which tin accounts for 6wt% of the copper alloy powder by weight; the iron alloy powder includes iron and nickel elements, of which nickel accounts for 5wt% of the iron alloy powder by weight.

[0117] The method for preparing a brake pad in an embodiment of the present invention comprises the following steps:

[0118] S1. Prepare steel back and frame;

[0119] S2. According to the proportion, copper powder and tin powder are put into a high-speed mixer for high-speed mixing to obtain copper alloy powder, the mixing time is set to 5 min, the mixing speed is set to 2500 rpm, and iron powder and nickel powder are mixed at high speed to obtain ferroalloy powder, the mixing time is set to 5 min, and the mixing speed is set to 1000 rpm;

[0120] S3, putting the semi-graphitized carburizer particles, copper alloy powder and ferroalloy powder into a horizontal grid drum mixer for internal kneading and mixing to obtain a mixed powder, the mixing time is set to 20 min, the internal kneading temperature is set to 40° C., and the mixing speed is set to 15 rpm;

[0121] S4, V-shaped mixing of the mixed powder, high carbon ferrochrome, alumina, molybdenum powder, tungsten powder and binder to obtain a final mixed total powder, the mixing time is set to 45 min, and the mixing speed is set to 25 rpm;

[0122] The binder is kerosene, and the amount of kerosene added is 0.7wt% of the total amount of the mixed powder.

[0123] S5, placing the mixed total powder in a mold at room temperature for high pressure molding to obtain a friction body green body, the high pressure molding pressure is 10Mpa, and the holding time is 7 seconds;

[0124] S6. Place the friction body green body and the skeleton in a chain belt pressure sintering furnace for sintering. The chain belt speed is set to 60 mm / min, the sintering pressure is set to 0.15 MPa, and the sintering is performed by step-by-step heating. When each section reaches the set temperature of the section, the product is placed on the chain belt and pressurized for sintering. The step-by-step heating specifically includes:

[0125] The chain belt pressure sintering furnace is divided into four sections, the first section is 1200mm, the temperature is 400℃, the second section is 1200mm, the temperature is 600℃, the third section is 1200mm, the temperature is 600℃, and the fourth section is 3600mm, the temperature is 1000℃;

[0126] Then it is quickly cooled to below 20℃ by a cooling jacket and then taken out of the furnace. Ammonia decomposition gas is used for protection during the sintering and cooling processes. After sintering and cooling, friction particles are obtained.

[0127] S7. First, install the disc-shaped spring piece and the sound insulation pad into the disc-shaped spring piece installation groove with the locking hole on the front side of the steel back in sequence, then insert the friction particle locking pin through the sound insulation pad and the disc-shaped spring piece into the locking hole on the steel back in sequence, finally turn over the semi-finished brake pad, and insert the retaining spring into the thin neck of the locking pin to obtain the brake pad for hydrogen energy train braking.

[0128] Example 4

[0129] An embodiment of the present invention provides a brake pad for a hydrogen energy train, comprising a dovetail pin-shaped steel back and a plurality of friction particles, wherein the friction particles comprise a skeleton and a friction body, the friction body is fixed on the skeleton, and the friction particles are fixed on the steel back through the skeleton.

[0130] The friction body is prepared from the following raw material components, based on the weight percentage of the friction body: 50wt% copper alloy powder, 25wt% iron alloy powder, 12wt% semi-graphitized carburizer particles, 1.5wt% molybdenum powder, 0.5wt% tungsten powder, 9wt% high carbon ferrochrome, and 2wt% alumina.

[0131] The copper alloy powder includes copper and tin elements, of which tin accounts for 4wt% of the copper alloy powder by weight; the iron alloy powder includes iron and nickel elements, of which nickel accounts for 6wt% of the iron alloy powder by weight.

[0132] The method for preparing a brake pad in an embodiment of the present invention comprises the following steps:

[0133] S1. Prepare steel back and frame;

[0134] S2. According to the proportion, copper powder and tin powder are put into a high-speed mixer for high-speed mixing to obtain copper alloy powder, the mixing time is set to 5 min, the mixing speed is set to 2500 rpm, and iron powder and nickel powder are mixed at high speed to obtain ferroalloy powder, the mixing time is set to 5 min, and the mixing speed is set to 1000 rpm;

[0135] S3, putting the semi-graphitized recarburizer particles, copper alloy powder and ferroalloy powder into a horizontal grid drum mixer for internal kneading and mixing to obtain a mixed powder, the mixing time is set to 15 min, the internal kneading temperature is set to 70° C., and the mixing speed is set to 25 rpm;

[0136] S4, V-shaped mixing of the mixed powder, high carbon ferrochrome, alumina, molybdenum powder, tungsten powder and binder to obtain a final mixed total powder, the mixing time is set to 40 min, and the mixing speed is set to 30 rpm;

[0137] The binder is kerosene, and the amount of kerosene added is 0.7wt% of the total amount of the mixed powder.

[0138] S5, placing the mixed total powder in a mold at room temperature for high pressure molding to obtain a friction body green body, the high pressure molding pressure is 8 MPa, and the holding time is 8 seconds;

[0139] S6. Place the friction body green body and the skeleton in a chain belt pressure sintering furnace for sintering. The chain belt speed is set to 60 mm / min, the sintering pressure is set to 0.15 MPa, and the sintering is performed by step-by-step heating. When each section reaches the set temperature of the section, the product is placed on the chain belt and pressurized for sintering. The step-by-step heating specifically includes:

[0140] The chain belt pressure sintering furnace is divided into four sections, the first section is 1200mm, the temperature is 450℃, the second section is 1200mm, the temperature is 650℃, the third section is 1200mm, the temperature is 650℃, and the fourth section is 3600mm, the temperature is 1050℃;

[0141] Then it is quickly cooled to below 20℃ by a cooling jacket and then taken out of the furnace. Ammonia decomposition gas is used for protection during the sintering and cooling processes. After sintering and cooling, friction particles are obtained.

[0142] S7. First, install the disc-shaped spring piece and the sound insulation pad into the disc-shaped spring piece installation groove with the locking hole on the front side of the steel back in sequence, then insert the friction particle locking pin through the sound insulation pad and the disc-shaped spring piece into the locking hole on the steel back in sequence, finally turn over the semi-finished brake pad, and insert the retaining spring into the thin neck of the locking pin to obtain the brake pad for hydrogen energy train braking.

[0143] Example 5

[0144] An embodiment of the present invention provides a brake pad for a hydrogen energy train, comprising a dovetail pin-shaped steel back and a plurality of friction particles, wherein the friction particles comprise a skeleton and a friction body, the friction body is fixed on the skeleton, and the friction particles are fixed on the steel back through the skeleton.

[0145] The friction body is prepared from the following raw material components, calculated by weight percentage of the friction body: 40wt% copper alloy powder, 25wt% iron alloy powder, 17wt% semi-graphitized carburizer particles, 2wt% molybdenum powder, 2wt% tungsten powder, 10wt% high carbon ferrochrome, and 4wt% zirconium oxide.

[0146] The copper alloy powder includes copper and tin elements, of which tin accounts for 5wt% of the copper alloy powder by weight; the iron alloy powder includes iron and nickel elements, of which nickel accounts for 4wt% of the iron alloy powder by weight.

[0147] The method for preparing a brake pad in an embodiment of the present invention comprises the following steps:

[0148] S1. Prepare steel back and frame;

[0149] S2. According to the proportion, copper powder and tin powder are put into a high-speed mixer for high-speed mixing to obtain copper alloy powder, the mixing time is set to 3 min, the mixing speed is set to 1000 rpm, and iron powder and nickel powder are mixed at high speed to obtain ferroalloy powder, the mixing time is set to 5 min, and the mixing speed is set to 1000 rpm;

[0150] S3, putting the semi-graphitized carburizer particles, copper alloy powder and ferroalloy powder into a horizontal grid drum mixer for internal kneading and mixing to obtain a mixed powder, the mixing time is set to 20 min, the internal kneading temperature is set to 30° C., and the mixing speed is set to 30 rpm;

[0151] S4, V-shaped mixing of the mixed powder, high carbon ferrochrome, alumina, molybdenum powder, tungsten powder and binder to obtain a final mixed total powder, the mixing time is set to 50 min, and the mixing speed is set to 15 rpm;

[0152] The binder is kerosene, and the amount of kerosene added is 0.7wt% of the total amount of the alloyed mixed powder.

[0153] S5, placing the mixed total powder in a mold at room temperature for high pressure molding to obtain a friction body green body, the high pressure molding pressure is 12 MPa, and the holding time is 5 seconds;

[0154] S6. Place the friction body green body and the skeleton in a chain belt pressure sintering furnace for sintering. The chain belt speed is set to 60 mm / min, the sintering pressure is set to 0.15 MPa, and the sintering is performed by step-by-step heating. When each section reaches the set temperature of the section, the product is placed on the chain belt and pressurized for sintering. The step-by-step heating specifically includes:

[0155] The chain belt pressure sintering furnace is divided into four sections, the first section is 1200mm, the temperature is 400℃, the second section is 1200mm, the temperature is 500℃, the third section is 1200mm, the temperature is 600℃, and the fourth section is 3600mm, the temperature is 900℃;

[0156] Then it is quickly cooled to below 20℃ by a cooling jacket and then taken out of the furnace. Ammonia decomposition gas is used for protection during the sintering and cooling processes. After sintering and cooling, friction particles are obtained.

[0157] S7. First, install the disc-shaped spring piece and the sound insulation pad into the disc-shaped spring piece installation groove with the locking hole on the front side of the steel back in sequence, then insert the friction particle locking pin through the sound insulation pad and the disc-shaped spring piece into the locking hole on the steel back in sequence, finally turn over the semi-finished brake pad, and insert the retaining spring into the thin neck of the locking pin to obtain the brake pad for hydrogen energy train braking.

[0158] Example 6

[0159] An embodiment of the present invention provides a brake pad for a hydrogen energy train, comprising a dovetail pin-shaped steel back and a plurality of friction particles, wherein the friction particles comprise a skeleton and a friction body, the friction body is fixed on the skeleton, and the friction particles are fixed on the steel back through the skeleton.

[0160] The friction body is prepared from the following raw material components, based on the weight percentage of the friction body: 42wt% copper alloy powder, 22wt% iron alloy powder, 20wt% semi-graphitized carburizer particles, 0.5wt% molybdenum powder, 1.5wt% tungsten powder, 12wt% high carbon ferrochrome, and 2wt% titanium oxide.

[0161] The copper alloy powder includes copper and tin elements, of which tin accounts for 4.7wt% of the copper alloy powder by weight percentage; the iron alloy powder includes iron and nickel elements, of which nickel accounts for 4.5wt% of the iron alloy powder by weight percentage.

[0162] The method for preparing a brake pad in an embodiment of the present invention comprises the following steps:

[0163] S1. Prepare steel back and frame;

[0164] S2. According to the proportion, copper powder and tin powder are put into a high-speed mixer for high-speed mixing to obtain copper alloy powder, the mixing time is set to 4 min, the mixing speed is set to 1800 rpm, and iron powder and nickel powder are mixed at high speed to obtain ferroalloy powder, the mixing time is set to 3.5 min, and the mixing speed is set to 2200 rpm;

[0165] S3, putting the semi-graphitized recarburizer particles, copper alloy powder and ferroalloy powder into a horizontal grid drum mixer for internal kneading and mixing to obtain a mixed powder, the mixing time is set to 10 min, the internal kneading temperature is set to 80° C., and the mixing speed is set to 15 rpm;

[0166] S4, V-shaped mixing of the mixed powder, high carbon ferrochrome, alumina, molybdenum powder, tungsten powder and binder to obtain a final mixed total powder, the mixing time is set to 50 min, and the mixing speed is set to 15 rpm;

[0167] The binder is kerosene, and the amount of kerosene added is 0.7wt% of the total amount of the alloyed mixed powder.

[0168] S5, placing the mixed total powder in a mold at room temperature for high pressure molding to obtain a friction body green body, the high pressure molding pressure is 10Mpa, and the holding time is 7 seconds;

[0169] S6. Place the friction body green body and the skeleton in a chain belt pressure sintering furnace for sintering. The chain belt speed is set to 60 mm / min, the sintering pressure is set to 0.1 MPa, and the sintering is performed by step-by-step heating. When each section reaches the set temperature of the section, the product is placed on the chain belt and pressurized for sintering. The step-by-step heating specifically includes:

[0170] The chain belt pressure sintering furnace is divided into four sections, the first section is 1200mm, the temperature is 350℃, the second section is 1200mm, the temperature is 550℃, the third section is 1200mm, the temperature is 600℃, and the fourth section is 3600mm, the temperature is 950℃;

[0171] Then it is quickly cooled to below 20℃ by a cooling jacket and then taken out of the furnace. Ammonia decomposition gas is used for protection during the sintering and cooling processes. After sintering and cooling, friction particles are obtained.

[0172] S7. First, install the disc-shaped spring piece and the sound insulation pad into the disc-shaped spring piece installation groove with the locking hole on the front side of the steel back in sequence, then insert the friction particle locking pin through the sound insulation pad and the disc-shaped spring piece into the locking hole on the steel back in sequence, finally turn over the semi-finished brake pad, and insert the retaining spring into the thin neck of the locking pin to obtain the brake pad for hydrogen energy train braking.

[0173] The friction bodies for hydrogen energy train brake pads of Examples 1 to 6 are composed of the components shown in Table 1.

[0174] Table 1 Ingredients composition of Example 1 to Example 6 (wt%)

[0175]

[0176] The beneficial effects of the present invention are verified by comparing the comparative examples below.

[0177] Comparative Example 1

[0178] The raw material composition and preparation method of Comparative Example 1 are basically the same as those of Example 1, except that an equal amount of flake graphite is used in the preparation step S3 to replace the semi-graphitized recarburizer particles, and the other amounts remain unchanged.

[0179] Comparative Example 2

[0180] The raw material composition and preparation method of Comparative Example 2 are basically the same as those of Example 1, except that when preparing the copper alloy powder in step S2, an equal amount of tin powder is replaced by copper powder, that is, only 48 wt % of copper powder is used, and tin powder is missing.

[0181] Comparative Example 3

[0182] The raw material composition and preparation method of Comparative Example 3 are basically the same as those of Example 1, except that when preparing the ferroalloy powder in step S2, the nickel powder is replaced by iron powder in equal amounts, that is, only 24 wt % of iron powder is used, and nickel powder is missing.

[0183] Comparative Example 4

[0184] The raw material composition and preparation method of Comparative Example 4 are basically the same as those of Example 1, except that: when preparing copper alloy powder in step S2, an equal amount of tin powder is replaced by copper powder; when preparing iron alloy powder, an equal amount of nickel powder is replaced by iron powder.

[0185] Comparative Example 5

[0186] The raw material composition and preparation method of Comparative Example 5 are basically the same as those of Example 1, except that: in the friction body, the copper alloy powder accounts for 38% by weight of the copper alloy powder, of which the tin element accounts for 5.26wt% of the copper alloy powder, and the iron alloy powder accounts for 34% by weight of the iron alloy powder, of which the nickel element accounts for 2.94wt% of the iron alloy powder.

[0187] Comparative Example 6

[0188] The raw material composition and preparation method of Comparative Example 6 are basically the same as those of Example 1, except that: in the friction body, the copper alloy powder accounts for 68%, of which the tin element accounts for 2.94wt% of the copper alloy powder by weight; the iron alloy powder accounts for 4%, of which the nickel element accounts for 25wt% of the iron alloy powder by weight.

[0189] Performance Testing

[0190] The Renk brake dynamic test bench of Hunan Shixin New Materials Co., Ltd. was used to carry out friction and wear tests on the brake pad products of Examples 1 to 6 and Comparative Examples 1 to 6. The measurement method refers to Table C.5 of "TJ / CL307-2019 Interim Technical Conditions for EMU Brake Pads".

[0191] During the test, a carbon ceramic brake disc with a diameter of 680 mm, a brake friction radius of 277 mm, a maximum braking pressure of 36 kN on both sides, a disc load of 8.5 t, a wheel diameter of 860 mm, and a maximum test speed of 275 km / h was used. The measurement results of Examples 1 to 6 are shown in Table 2, and the measurement results of Comparative Examples 1 to 6 are shown in Table 3.

[0192] Table 2 Brake pad test results of Examples 1 to 6

[0193] From the data in Table 2, it can be seen that the average friction coefficient of the brake pads in Examples 1 to 6 under different braking conditions is between 0.33 and 0.42, and the friction coefficient does not fluctuate much when the initial braking speed and braking pressure change. The stability of the friction coefficient is high, which can ensure effective braking during use. In addition, the wear of the brake pad is 0.1 cm 3 / MJ~0.2cm 3 / MJ, the wear is low and the service life is long. The maximum noise during braking is kept below 72dB, meeting the noise requirements of the train.

[0194] Table 3 Brake pad test results of Comparative Examples 1 to 6

[0195]

[0196] It can be seen from the data in Table 3 that in Comparative Example 1, after using an equal amount of flake graphite to replace the semi-graphitized recarburizer particles, the friction coefficient is generally lower, especially the average friction coefficient under a high braking pressure of 36 kN and the average friction coefficient under high-speed conditions of 250 km / h and 275 km / h are both lower than the required lower limit.

[0197] In Comparative Example 2, copper powder is used instead of copper alloy powder, and tin powder is missing. Compared with the copper-tin alloy matrix, the copper matrix has lower mechanical strength, poorer wear resistance, and increased wear, so that the average friction coefficient of the prepared brake pad is generally lower than that of Example 1, and the average friction coefficient of the brake pad under high braking pressure (36kN) and high speed conditions (250km / h and 275km / h) is lower than the required lower limit of 0.29. The maximum noise tested is increased compared with 72dB in Example 1, and it cannot be well adapted to the high temperature and high pressure service conditions during train braking.

[0198] In Comparative Example 3, iron powder is used instead of iron alloy powder, and nickel powder is missing. Compared with Example 1, the wear amount of the brake pad in Comparative Example 3 increases (0.28 cm 3 / MJ), the average friction coefficient is reduced, and the average friction coefficient under high braking pressure (36kN) and high speed conditions (250km / h and 275km / h) is lower than the required lower limit of 0.29. Compared with the iron-nickel alloy matrix, the iron matrix of Comparative Example 3 has a low high-temperature strength under heavy load, high speed and high temperature, so that the brake pad prepared cannot effectively ensure the stability of the friction coefficient under high temperature and high pressure conditions of high-speed braking of trains.

[0199] In Comparative Example 4, copper powder is used instead of copper alloy powder, iron powder is used instead of iron alloy powder, and tin powder and nickel powder are missing. The brake pad of Comparative Example 4 lacks the metal alloying to strengthen the matrix, resulting in a decrease in matrix strength and an increase in wear (0.33 cm 3 / MJ), which is twice that of Example 1, and cannot effectively ensure the stability of the friction coefficient. The average friction coefficient of the brake pad under low-speed conditions (50km / h) exceeds the upper limit of 0.44, and the average friction coefficient under high-speed conditions (250km / h and 275km / h) with large braking pressure (36kN) is lower than the required lower limit of 0.29. The friction coefficient of the brake pad exceeding the upper limit is likely to cause the braking process to be too violent, causing damage to the wheel or brake disc. When the friction coefficient is lower than the lower limit, the brake pad cannot generate enough friction to slow down or stop the train, which will lead to an increase in the braking distance and increase the risk of collision. This also causes the brake pad to generate too much noise during the train braking process, and the maximum noise tested is increased compared to 72dB in Example 1.

[0200] In comparative example 5, the proportion of iron element is increased when preparing alloy powder, which reduces the thermal conductivity of the brake pad, resulting in an increase in the temperature of the brake system, thereby reducing the friction coefficient of the brake pad under high temperature and high pressure conditions of high-speed braking of the train. Compared with Example 1, the average friction coefficient of the brake pad of comparative example 5 is generally low, and the average friction coefficient under high-speed conditions (250km / h and 275km / h) with large braking pressure (36kN) is lower than the required lower limit of 0.29, and the maximum noise tested is increased compared with 72dB of Example 1, which cannot be well adapted to the high temperature and high pressure service conditions of train braking.

[0201] In Comparative Example 6, when preparing the alloy powder, the proportion of copper element increased, and the proportion of iron element dropped sharply. The mechanical strength of copper is not high, so the prepared brake pad cannot have good high-temperature strength, resulting in a sharp drop in the static friction coefficient of the brake pad, which seriously affects the slope parking and parking brake of the train.

[0202] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A friction body, It is characterized in that The friction body is prepared from the following raw material components in terms of weight percentage: 60wt% to 75wt% of a base component, 11wt% to 16wt% of a friction component, 12wt% to 20wt% of a reinforcing component and 2wt% to 4wt% of a stabilizing component; The matrix components are copper alloy powder and iron alloy powder. The alloyed copper-iron alloy powder, in terms of weight percentage of the friction body, comprises 40wt% to 50wt% of the copper alloy powder, and 20wt% to 25wt% of the iron alloy powder. The reinforcing component comprises semi-graphitized recarburizer particles.

2. The friction body according to claim 1, Features: The copper alloy powder includes copper powder and tin powder, and the tin powder accounts for 4wt% to 6wt% of the copper alloy powder by weight percentage; the iron alloy powder includes iron powder and nickel powder, and the nickel powder accounts for 4wt% to 6wt% of the iron alloy powder by weight percentage.

3. The friction body according to claim 1, Features: The friction components include a main friction component and a secondary friction component. The main friction component includes high carbon ferrochrome, and the secondary friction component includes any one of aluminum oxide, zirconium oxide and titanium oxide. The stabilizing component includes molybdenum powder and tungsten powder.

4. The friction body according to claim 3, Features: Calculated in weight percentage of the friction body, the weight percentage of the main friction component is 9wt% to 12wt%, and the weight percentage of the secondary friction component is 2wt% to 4wt%.

5. The friction body according to claim 3 or 4, Features: The particle size of the semi-graphitized recarburizer particles is 30-100 meshes, and the sulfur content of the semi-graphitized recarburizer particles is 0.1-0.3%; And / or, the particle size of the high carbon ferrochrome is ≤60 mesh, the chromium content of the high carbon ferrochrome is 68wt%-73wt%, the carbon content is 7wt%-9wt%, the iron content is 20wt%-23wt%, and the particle sizes of the aluminum oxide, the zirconium oxide, and the titanium oxide are all 100-200 mesh; And / or, the particle size of the molybdenum powder is ≤325 mesh, and the particle size of the tungsten powder is ≤325 mesh.

6. A method for preparing a friction body, Features: The friction body applied to any one of claims 1 to 5 comprises: According to the proportion, copper powder and tin powder are mixed at a high speed of 1000 rpm to 3000 rpm for 3 to 5 minutes to obtain copper alloy powder, and iron powder and nickel powder are mixed at a high speed of 1000 rpm to 3000 rpm for 3 to 5 minutes to obtain iron alloy powder; The semi-graphitized recarburizer particles, copper alloy powder and iron alloy powder are mixed by internal kneading, the mixing speed is set to 15 rpm to 30 rpm, the mixing time is set to 10 to 20 min, and the internal kneading temperature is set to 0 to 80° C. to obtain a mixed powder; The stabilizing component, the friction component, the alloyed mixed powder and the binder are mixed in a V-shape, the mixing speed is set to 15 rpm to 30 rpm, and the mixing time is set to 40 to 50 min to obtain a mixed total powder; The mixed total powder is placed in a mold at room temperature for high pressure molding, the pressure is set to 7MPa-15MPa, and the pressure holding time is 3-10 seconds to obtain a friction body green body, which is then pressurized and sintered to form a friction body.

7. The method for preparing the friction body according to claim 6, It is characterized in that The binder is kerosene, and the amount of the binder added is 0.7wt% of the total amount of the mixed powder.

8. A brake pad, It is characterized in that include: A steel back and friction particles, wherein the friction particles include a frame and a friction body as claimed in any one of claims 1 to 5, and the friction body is fixed on the frame; The friction particles are fixed on the steel back through the framework.

9. A method for preparing a brake pad, It is characterized in that The brake pad as claimed in claim 8 comprises the following steps: Prepare the steel back and the frame; The friction body green body and the skeleton are pressurized and sintered under protective gas protection to obtain friction particles; The friction particles are fixed on the steel back to obtain a brake pad.

10. The method for preparing a brake pad according to claim 9, Features: The step of pressurizing and sintering the friction body green body and the skeleton comprises: The friction body green body and the skeleton are placed in a chain belt type pressure sintering furnace for sintering. When the chain belt type pressure sintering furnace is opened, a protective atmosphere is first introduced, the chain belt speed is set to 60 mm / min, the sintering pressure is set to 0.1-0.2 MPa, and the sintering adopts a segmented step-by-step temperature increase. When each segment reaches the set temperature of the segment, the product is placed on the chain belt and pressurized for sintering. The segmented step-by-step temperature increase specifically includes: The chain-belt pressure sintering furnace is divided into four sections. The first section is 1200mm, with a temperature of 300℃~500℃, the second section is 1200mm, with a temperature of 500℃~700℃, the third section is 1200mm, with a temperature of 500℃~700℃, and the fourth section is 3600mm, with a temperature of 900℃~1100℃.